Organizational Culture Female Workers Glass Ceiling: The Effects On Career Satisfaction And Work Engagement - Ririsma Sihombing; Agnes Neisha Kirani; Melviana (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – One crucial aspect that needs constant improvement is the calibre of human resources. Quality resources that are in line with recent advancements, particularly digital transformation, are required in the present 4.0 era. Men and women still participate in the workforce at a significantly different rate. It is imperative that continuous efforts be made to increase women's employability. Aim – Analyzing and identifying the organizational culture of the glass ceiling for female workers career satisfaction and work engagement is the goal of this study. Design /Methodology /Approach – Up to 340 female employees who worked by or had status as workers in a company took part the survey. Purposive sampling, formerly known as sampling based on judgement, was the sample strategy employed. A 5-point Likert scale survey had been used to collect data, and it was distributed online via a Google Form. SMART-PLS was used for SEM analysis, and SPSS was used for descriptive analysis. Findings – Glass Ceiling is influenced by Organization Culture, Glass Ceiling influences Career Satisfaction and Work Engagement, and Organization Culture influences Career Satisfaction and Work Engagement. In this way, Glass Ceiling acts as a mediator between Organization Culture and Career Satisfaction. This indicates that glass ceiling can operate as a mediator between Organizational culture and career satisfaction. Next, Glass ceiling acts as a mediator connecting Organization Culture and Work Engagement, showing that Glass ceiling can act as a mediator between Organization Culture and Work Engagement. Conclusion - This study also found that organizational culture not only directly influences job satisfaction and engagement, but also indirectly through the mediating role of the glass ceiling. This means that a non-inclusive organizational culture reinforces these barriers, which then negatively impacts women's work experiences. Research Implications – According to this study, a non-inclusive corporate culture perpetuates the glass ceiling, which has a detrimental effect on women's involvement and job happiness. It follows that companies must reassess promotion policies, foster a gender-equal workplace culture, and assist women in advancing their careers. Policies that promote a more equal and inclusive workplace for people of all genders can also be influenced by these findings. Research Limitations – The collection of data has been limited to female employees, and there are currently limited samples, requiring more comprehensive studies on a greater proportion of female employees.